2021
DOI: 10.1097/wnr.0000000000001753
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Iridoids effective fraction of Valeriana jatamansi Jones on movement function in rats after acute cord injury and the related mechanism

Abstract: Objectives Spinal cord injury (SCI) is a disastrous central nervous system (CNS) disorder, which was intimately associated with oxidative stress. Studies have confirmed that Iridoids Effective Fraction of Valeriana jatamansi Jones (IEFV) can scavenge reactive oxygen species. This study aimed to confirm the efficacy of IEFV in ameliorating SCI. MethodsFor establish the SCI model, the Sprague-Dawley rats underwent a T10 laminectomy with transient violent oppression by aneurysm clip. Then, the rats received IEFV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, it is devoid of toxicological side effects and evident drug dependence ( Yu et al, 2015 ). Our previous research has established that IRFV can enhance motor function recovery and elevate the expression levels of brain-derived neurotrophic factor and nerve growth factor in SCI rats ( Xiong et al, 2022 ). In this study, aligning with prior findings, our results corroborate that IRFV enhances motor function in SCI rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is devoid of toxicological side effects and evident drug dependence ( Yu et al, 2015 ). Our previous research has established that IRFV can enhance motor function recovery and elevate the expression levels of brain-derived neurotrophic factor and nerve growth factor in SCI rats ( Xiong et al, 2022 ). In this study, aligning with prior findings, our results corroborate that IRFV enhances motor function in SCI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Renowned for its analgesic, antidiarrheal, and sedative properties, it holds a venerable position in herbal medicine ( Wang et al, 2018 ). Our preceding research revealed that the Iridoid-rich fraction from Valeriana jatamansi Jones (IRFV) significantly enhances motor function recovery following SCI in rat models, reduce inflammatory response, and promote the expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), with the optimal efficacy noted at a dosage of 10 mg/kg ( Xiong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, VJJ has displayed an effect on the central nervous system through various molecular mechanisms [ 42 ] and demonstrated improvement in the recovery of motor function in rats after SCI. [ 11 ] The study adopted a network pharmacological approach to predict the molecular mechanism of VJJ in SCI and added molecular docking techniques to provide a new idea and theoretical basis for further in-depth investigation of the application of VJJ in SCI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 ] VJJ is a Chinese herbal medicine with promising future development. Additionally, VJJ can promote the recovery of hind limb motor function in rats with acute SCI, [ 11 ] counteract oxidative stress caused by SCI, [ 12 ] and ease neuronal apoptosis and pyroptosis, [ 13 ] all of which have neuroprotective effects. [ 14 ] However, the specific molecular mechanism of action of VJJ in SCI remains unclear.…”
Section: Introductionmentioning
confidence: 99%